2020
DOI: 10.1093/jac/dkaa334
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir and daclatasvir compared with standard of care in the treatment of patients admitted to hospital with moderate or severe coronavirus infection (COVID-19): a randomized controlled trial

Abstract: Background Currently no effective antiviral therapy has been found to treat COVID-19. The aim of this trial was to assess if the addition of sofosbuvir and daclatasvir improved clinical outcomes in patients with moderate or severe COVID-19. Methods This was an open-label, multicentre, randomized controlled clinical trial in adults with moderate or severe COVID-19 admitted to four university hospitals in Iran. Patients were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
119
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(125 citation statements)
references
References 31 publications
(24 reference statements)
1
119
0
1
Order By: Relevance
“…46 The structures of the SARS-CoV-2 RNA-dependent RNA polymerase nsp12 and its complex with nsp7 and nsp8 have been determined by cryo-EM, 49,50 Daclatasvir (DCV) to treat moderate or severe COVID-19 patients. 59 These investigators showed that SOF/DCV treatment increased 14-day clinical recovery rates and reduced hospital stays. Two similar SOF/DCV clinical trials were also performed and provided evidence that this drug combination may have some benefit; 60,61 the authors recommended that larger well-controlled randomized trials are necessary to confirm their results.…”
Section: F I G U R E 4 Incorporation Of 2'-fme-utp 3'-f-dttp and 3'mentioning
confidence: 99%
“…46 The structures of the SARS-CoV-2 RNA-dependent RNA polymerase nsp12 and its complex with nsp7 and nsp8 have been determined by cryo-EM, 49,50 Daclatasvir (DCV) to treat moderate or severe COVID-19 patients. 59 These investigators showed that SOF/DCV treatment increased 14-day clinical recovery rates and reduced hospital stays. Two similar SOF/DCV clinical trials were also performed and provided evidence that this drug combination may have some benefit; 60,61 the authors recommended that larger well-controlled randomized trials are necessary to confirm their results.…”
Section: F I G U R E 4 Incorporation Of 2'-fme-utp 3'-f-dttp and 3'mentioning
confidence: 99%
“…Other investigators have since demonstrated the ability of Sofosbuvir to inhibit SARS-CoV-2 replication in lung and brain cells 18,19 , and COVID-19 clinical trials with EPCLUSA 20 and with Sofosbuvir plus Daclatasvir 21 have been initiated in several countries. Recently, Sadeghi et al reported encouraging results from a clinical trial using Sofosbuvir (SOF) and Daclatasvir (DCV) as a potential combination treatment for moderate or severe COVID-19 patients 22 . In a study involving 66 patients, these investigators showed that SOF/ DCV treatment increased 14-day clinical recovery rates and reduced the length of hospital stays.…”
mentioning
confidence: 99%
“…Subgenomic mRNAs are produced by discontinuous transcrip-tion, a process characteristic of this RdRp, which favors recombination. Compounds such as remdesivir, favipiravir, and sofosbuvir block this enzyme [39][40][41]45]. The subgenomic mRNAs are then translated into protein.…”
Section: Targeting Viral Enzymesmentioning
confidence: 99%
“…Remdesivir similarly to sofosbuvir, a direct-acting antiviral used in HCV therapy, is a chain-terminating nucleotide analog. These drugs produce their therapeutic effect by directly interacting with the RdRp and incorporating the active form of the inhibitor into the growing RNA strand, preventing the replication to continue [40,41]. Several clinical trials have been conducted evaluating the activity of remdesivir and other direct-acting antivirals used in HCV against SARS-CoV-2 [42].…”
mentioning
confidence: 99%